Prediction of deformations by means of finite element computation and stress path testing technique - Kilic, H; Yildirim, S (A A BALKEMA PUBLISHERS, 2001)
As a first step in this investigation the deformations of foundation layers underneath different sections of Alibey Dam, were predicted by means of numerical analysis. The foundation soil was modelled by using plain-strain finite element method and stress-strain-consolidation behaviour was calculated by means of coupled analyses utilising Plaxis programme developed for such problems. In the second step, the vertical and lateral effective stresses predicted fro-in the first step were used in stress path application of the experimental work in the laboratory. Block samples were brought to the piedicted initial field stress conditions in an extended type of Rowe Cell. The triaxial test specimens prepared from these blocks were tested wider anisotropic stress increments allowing consolidation periods in accordance with the field conditions. In five sections (B22, B18, B23, B24 and B9 axis) considering two different depths in each, the vertical strains predicted from numerical analyses, experimental work and the field measurements were compared and found to be in good aggrement.
Keywords: Engineering